A new method for baseline extraction of Manchu word. (3rd May 2016) - Zheng, Rui-Rui; Li, Min; Xu, Shuang; Hu, Yan-Xia; Wu, Bao-Chun
Abstract: The baseline of Manchu word extracted using project profile histogram often shifts from its accuracy position, and leads to segmentation errors. This paper proposes a new method for baseline extraction of Manchu word after studying and fusing morphology, Hough transform and max-run-length-proportion method. Experiments on 400 Manchu word images including 4 different Manchu fonts with 6 font sizes show that the extraction method proposed in this paper is effective and has strong adaptability. The extraction accuracy reaches 100% which is higher than other 2 compared methods. The new baseline extraction method is also useful for Mongolian, Arabic, etc. characters which also have baselines.